A signal processor made from DNA assembly and upconversion nanoparticle for pharmacokinetic study. (February 2022) - Yao, Chi; Tang, Jianpu; Zhu, Chenxu; Yang, Sen; Tang, Han; Dong, Luxi; Zhang, Chunzhi; Tang, Qianyun; Liu, Peifeng; Yang, Dayong
Highlights: The real-time drug-release monitoring is important for pharmacokinetic study toward clinical applications. The route of synthesis and functionalization of DNA-UCNP hybrid nanocomplex is simple and efficient. The particle size of nanocomplex can be controlled based on the new strategy of interfacial assembly. Ratiometric imaging is utilized for reducing the influence of local carrier concentration and microenvironment variation. Graphical Abstract: A signal processor was constructed via interfacial and epitaxial assembly of ultra-long DNA chain on UCNP, achieving accurate and reliable real-time quantitative drug-release monitoring in vivo, which minimized the fluctuation of complex biological microenvironment and dosage variation. ga1 Abstract: The real-time drug-release monitoring is important for pharmacokinetic study toward clinical applications. The accuracy is usually severely affected by the fluctuation of complex biological microenvironment and dosage variation. Herein, a novel signal processor, upconversion nanoparticle (UCNP)-DNA nanocomplex (UCDC) was constructed via rational DNA design, enabling NIR-excited real-time in vivo drug-release monitoring, and realizing real-time pharmacokinetic monitoring. The signal processor was constructed by interfacial assembly of circular DNA on UCNP and the subsequent epitaxial assembly of ultralong DNA. Ultralong DNA chain was programed with multiple desired functional regions: double-stranded region for chemotherapy drugs integrating, DNA aptamer for tumor cells targeting and hairpin/i-motif switchable structure for tumor microenvironment responsive drug release. Based on filter effect of loaded drug molecules, efficient switch of real-time drug-release to optical signal was realized. For signal output, the ratiometer of red upconversion emission (UCLR ) and NIR upconversion emission (UCLNIR ) was monitored (UCLR /UCLNIR ), with UCLNIR as an internal reference. In a breast cancer mouse model, the signal processor system achieved accurate and reliable localized drug-release monitoring, which effectively minimized the influence of the internal microenvironment and dosage variation.